Elevating the resistive memory from binary to ternary by introducing trialkyl phosphorus into binaphthol/ferrocene cores in their polystyrene composites. (December 2022) - Liu, Yuan-Zheng; Liu, Yue; Chen, Bin-Jun; Yang, Hai-Long; Lin, Xiao-Li; Li, Hao-Hong; Chen, Zhi-Rong
Abstract: The design of electrically active composites by modifying with functional groups with definite switching mechanism is the key to develop new multi-level memorizers. In this work, five binaphthol and two ferrocene derivants were embedded into polystyrene (PS) to fabricate FTO/binaphthol or ferrocene derivants@PS/Ag memory devices. Binaphthol derivants were firstly used in the memory devices, four of which exhibit binary resistive switching performance with ON/OFF ratio about 10 2.02 –10 2.44 . Interestingly, the trialkyl phosphorus-bearing one demonstrates excellent ternary memory performance with considerable ON2/ON1/OFF current ratio of 10 2.30 :10 4.22 :1, relatively low set voltages (0.99 and 1.68 V), good reliability, and high ternary yield of 66 %. Besides, two trialkyl phosphorus-containing ferrocene@PS composites also illustrate typical ternary resistive switching behavior with ON2/ON1/OFF current ratio of 10 2.34 :10 3.78 :1 and 10 1.97 :10 4.47 :1. Their ON1 states stem the increased dihedral angle of two naphthaline rings with the injection of hot carriers (for binaphthol derivants) and oxidation of ferrocene units (for ferrocene derivants). Interestingly, the ON2 states root from the flattening of tricoordinate phosphorus, which can enhance the conjugated degree, and as a result, higher conductivities. The rigid PS matrix can act as charge blocking layer and aggregation-inhibited species. The introduction of trialkyl phosphorus will be an efficient strategy for implementing low cost organic multi-level memorizer. Graphical Abstract: By introducing the trialkyl phosphorus groups into binaphthol/ferrocene cores, their resistive switching performance can be elevated from binary to ternary, based on which a universal strategy for implementing multi-level memory was proposed. ga1 Highlights: Binaphthol derivants were firstly fabricated as memory devices with ON/OFF ratio about 10 2.02 ~10 2.44 . FTO/RBDB@PS/Ag demonstrates excellent ternary memory performance with high ternary yield of 66 %. The presence of trialkyl phosphorus can elevate their resistive switching performance from binary to ternary. The increased dihedral angles and flattening of tricoordinate phosphorus are responsible for ternary conductive states. The universal strategy of introducing the trialkyl phosphorus for implementing multi-level memory was proposed.